ENSEÑANZA DE LA LECTURA, LA ESCRITURA Y LA ORALIDAD EN LAS DISCIPLINAS DE LA FACULTAD DE INFORMACIÓN Y COMUNICACIÓN: EL PROYECTO LESFIC. - Díaz, Damián; Fuster, Yanet; Bertolotti, Virginia; Arroyo, Lucía; Musto, Laura (Trabalhos em Lingüística Aplicada)
This article presents the results of a teacher training experience focused on reading, writing and orality, carried out by language teachers from the Facultad de Información y Comunicación of Universidad de la República with other teachers from the institution. It is based on two concepts: first, that teachers of the disciplines are fundamental actors in the teaching of literate academic practices and, second, that university reading, writing and oral practices, although they have common characteristics, are manifestations of disciplinary knowledge specific to each area. Our objective is to observe in what aspects the concerns about the teaching of reading, writing and orality of teachers of different subjects are common and in what aspects they differ, as well as to observe how this concern, when made explicit, is reflected in the creation of didactic resources for teaching in the disciplines. The data were collected through field notes during the individual exchange with eleven teachers of ten subjects using self-reflection questionnaires, reading and writing level descriptors, oral exchanges and the development of didactic resources. These records were qualitatively analysed, considering the variations between subjects regarding the concerns expressed. The results show a common body of concerns related mainly to writing, to a lesser extent to reading and, only in some cases, to orality. They also show concerns about specific language knowledge of the disciplinary areas in some teachers.